Hematological abnormalities in HIV infected individuals in correlation to CD4 counts and ART status - Thulasi, R Raman; Manimaran, D; Hemanathan, G; Afroz, Tameem; Sagar, Radha (Asian Journal of Medical Sciences, 2016)
Background: HIV is pandemic and remains as a public health concern for many decades. This infection though associated with many opportunistic infections and neoplasms, it is further complicated with marked hematological abnormalities. The aim of this study is to determine the magnitude & severity of hematological abnormalities in HIV infected individuals and also to analyze these abnormalities in correlation with the CD4 counts. We also compared these hematological abnormalities in patients on ART and those not on ART. Materials and Methods: The study was conducted for a period of one year, on 120 HIV positive cases including both patients on ART & not on ART. Controls with similar age and sex distribution was set up. The blood samples were collected and processed in an automated cell counter. The parameters were tabulated and analyzed with respect to CD4 count & ART status. Results: Among the total of 120 HIV cases, 77% had anemia, 21% had leucopenia and 5% had thrombocytopenia. The magnitude and severity of anemia, leucopenia, thrombocytopenia and other parameters was found to be more in patients not on ART, when compared to patients on ART. Similarly, the magnitude and severity of most of hematological abnormalities were inversely proportional to the CD4 count in non-ART cases but not with cases on ART. Conclusion: The basic hematological parameters can be used as a prospective screening test to assess the severity and progression of HIV infection when CD4 count is not available. These parameters can also be used to assess the response to anti-retroviral treatment. Therefore, these basic hematological investigations readily available at all medical centers are of great use while treating HIV infected patients. Asian Journal of Medical Sciences Vol.7(4) 2016 14-18